Pengaruh Kecerdasan Spiritual Terhadap Sikap Disiplin Santri Tahfidz di Asrama Hidayatul Qur’an Pondok Pesantren Darul Ulum Peterongan Jombang - Sapna Isabela; Dhikrul Hakim; Muhammad Makmun (Indo Publishing, 2025)
With the diversity of student characters, it can affect the level of discipline of students. A better understanding of the relationship between spiritual intelligence and discipline is expected to provide a positive contribution to the development of tahfidz education methods based on spiritual values. To produce memorizers of the Qur'an who are not only intellectually intelligent but also have character. This study analyzes the influence of spiritual intelligence on the discipline of tahfidz students at the Hidayatul Qur'an Dormitory, Darul Ulum Peterongan Islamic Boarding School, Jombang. The purpose of this study is to determine how much influence spiritual intelligence has on the discipline of tahfidz students. covering the issue of the importance of spiritual intelligence for happiness and discipline, as well as indications of a lack of discipline of students. Using quantitative methods, sampling was carried out with a random sampling technique of 12% of the total population, obtained 25 students from a population of 207 students, data were collected through documentation, observation and Likert scale questionnaires. Data analysis was carried out with percentages and simple linear regression. The results show that the students' spiritual intelligence is classified as